Usaha Budi Daya Tanaman Kopi Dalam Meningkatkan Pendapatan Masyarakat Desa Wolofeo Kecamatan Detusoko Kabupaten Ende - Yosef Moan Banda (Program Studi Pendidikan Ekonomi, Universitas Flores, 2018)
This study aims to abtain a clear and detailed description of coffee cultivation in Wolofeo Village, Detusoko District, Ende Regency, and the income level of coffee farmers and the factors that hinder the business of coffee cultivation. The focus of the research is the coffee cultivation business in Wolofeo Village, how much the income level of the coffee farmer community and the inhibiting factors of coffee making cultivation. This type of research is qualitative and quantitative in an integrated manner. With the population are all citizens in the Wolofeo Village area, while the sample in the study were 20 people from 2 hamlets namely Nuasipi Hamlet with 10 people and Jalan Sumbi Hamlet as many as 10 people. Taking samples in this study is done by random sampling, which is a lottery system because all have the same opportunities. The instrument used for data collection in the form of observation, interview and questionnaires, then processed and analyzed using the produst moment correlation coefficient formula. The calculation results obtained by rxy = 0.673, this result is consulted with a table of r value “Product Moment” with subjects (N) = 20 people in a significant level of 5% = 0.444 and a significant level of 1% = 0.561 which is simplified as follows: 0.444 < 0.673 > 0.561. Thus it can be said that the business of coffee cultivation has an effect in increasing the income of the people of Wolofeo Village, Detusoko Subdistrict, Ende Regency, with a moderate correlation classification of between 0.40 – 0.70.